2004
DOI: 10.1210/jc.2003-031056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Tunisian Patients with a Classic Form of 21-Hydroxylase Deficiency: Identification of Four Novel Mutations and High Prevalence of Q318X Mutation

Abstract: Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders mainly due to defects in the steroid 21-hydroxylase (CYP21) gene. To determine the mutational spectrum in the Tunisian CAH population, the CYP21 active gene was analyzed in 51 unrelated patients using our cascade strategy (digestion by restriction enzyme, sequencing). All patients had a classical form of 21-hydroxylase deficiency. Mutations were detected in over 94% of the chromosomes examined. The most frequent mutation in the Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 34 publications
9
48
2
1
Order By: Relevance
“…Gene deletions and chimeric genes encompass 31.8% of all gene mutations. The I2G has been mentioned as the most frequent mutation in western European cohorts (White and Speiser, 2000); but with an exception, the Q318X mutation was frequent in our study, which corresponds to Tunisia (Kharrat et al, 2004) and confirms the previous study in Iran (Vakili et al, 2005). By far, the I172N mutation is associated with the SV form.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Gene deletions and chimeric genes encompass 31.8% of all gene mutations. The I2G has been mentioned as the most frequent mutation in western European cohorts (White and Speiser, 2000); but with an exception, the Q318X mutation was frequent in our study, which corresponds to Tunisia (Kharrat et al, 2004) and confirms the previous study in Iran (Vakili et al, 2005). By far, the I172N mutation is associated with the SV form.…”
supporting
confidence: 89%
“…The PCR products were purified by ethanol precipitation protocols. Primers used were P1, P2, P5, P6, P10, (Kharrat et al, 2004) 3na, 4 ns, and 7na (Wilson et al, 1995b). Combination of these primers covered the whole coding and intronic sequences.…”
Section: Direct Sequencingmentioning
confidence: 99%
“…8 More than half of our female subjects showed Prader score III virilization. Similar to our study, Bajpai et al 18 reported Prader score III virilization in 52.7% of subjects, Kharrat et al 19 reported Prader score III and Prada score IV in 22 and 45% of the subjects respec-A. Deletion/LGC Figure 2.…”
Section: Discussionsupporting
confidence: 89%
“…The highest incidence of consanguinity that had ever been reported was in Tunisian population. 19 On the contrary, Koyama et al 16 reported that there were no consanguinity in CAH family in Japan. These facts emphasized that CYP21 gene and its pseudo gene are susceptible to genomic alteration due to adjacent structures and highly recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…The previously described mutations p.G424S, p.R408C, IVS2-2A>G, p.Ser170fs, p.R426H, p.H365Y, and p.W19X were observed in 35 nonrelated patients (23,24,25,26) (Table 2). Among them, the most frequent were the IVS2-2A>G, p.G424S, and p.R426H mutations.…”
Section: Mutations Not Derived From Gene Conversion Eventsmentioning
confidence: 80%